Field performance of bitumen emulsion Cold Central Plant Recycling (CCPR) mixture with same day and delayed overlay compared with traditional rehabilitation procedures. (December 2022) - Charmot, Stephane; Teh, Sek Yee; Haris, Rino Effendy Abu; Ayob, Mohd Azli; Ramzi, Mohammad Riad; Kamal, Dini Dayana Mustaffa; Atan, Azmi
Abstract: Cold Recycled Mixtures (CRM) offer many benefits, including cost-effectiveness and sustainability. Large existing Reclaimed Asphalt Pavement (RAP) stockpiles that represent an environmental and storage challenge can be used for bitumen emulsion Cold Central Plant Recycling (CCPR). A pavement rehabilitation demonstration project using Cold Recycled Mixture with Bitumen Emulsion (CRM-E) as binder course with 100% RAP was carried out on August 25, 2020. The project was divided into three sections to evaluate the mill and pave strategy using CRM-E as an alternative to traditional Hot Mixture Asphalt (HMA). The wearing course was the same asphalt concrete for the three sections. The difference between Section 1 and 2 that used CRM-E was to either pave the asphalt concrete overlay on the same day or to delay its application for 3 days to give additional time for the CRM-E to cure. Section 3 had no CCPR and consisted of two HMA layers. The field performance of the rehabilitated sections was monitored in 4 phases after 14 days, 3 months, 6 months and 12 months. The performance of the sections was assessed based on Falling Weight Deflectometer (FWD), field rutting measurements and cracking distress surveys. Cores were also taken over time to compare the CRM-E and HMA binder course properties in terms of resilient modulus, dynamic creep, indirect tensile strength and tensile strength ratio. The research showed that CRM-E and HMA performance was similar in terms of FWD deflections, field rutting, in situ cracking, and moisture resistance of the field cores. CRM-E showed superior performance in terms of resilient modulus and dynamic creep compared with asphalt concrete binder course based on testing of field cores taken after 6 and 12 months. The research showed that same day CRM-E HMA overlay is a viable construction option.